Teratogenicity and toxicity of the new BPA alternative TMBPF, and BPA, BPS, and BPAF in chick embryonic development - Kristen G. Harnett (Elsevier, 2021)
Bisphenol A (BPA) is a widely known, yet controversial reproductive toxin, capable of inducing reproductive, developmental, and somatic growth defects across species. Due to scientific findings and public concern, companies have developed BPA alternatives remarkably similar to BPA. However, these alternatives have had much less testing and oversight, yet they are already being mass-produced and used across industries from plastics to food-contact coatings. The newest one, tetramethyl bisphenol F (TMBPF), is the least well-studied and has never been investigated in embryological models, however it continues to be mass produced and found in various products. Here, we used the chicken embryotoxicity screening test to compare the toxicities and potencies of several BPA analogs including TMBPF. We exposed developing chicken (Gallus gallus domesticus) embryos in ovo, from embryonic day 5 to 12 (E5–12), to increasing concentrations of BPA, bisphenol S (BPS), bisphenol AF (BPAF), and TMBPF, from 0.003 to 30 μM, and analyzed their developmental and toxic effects. The bisphenols significantly impaired development, growth, and survival in a dose-dependent manner, even at low, environmentally relevant concentrations of 3–30 nM. There was severely reduced growth and developmental delay, with exposed embryos averaging half the size and weight of control vehicle-treated embryos. The most common and severe dysmorphologies were craniofacial, eye, gastrointestinal, and body pigmentation abnormalities. The bisphenols caused dose-dependent toxicity with the lowest LC50s (lethal concentration with 50% survival) ever demonstrated in chick embryos, at 0.83–2.92 μM. Notably, TMBPF was the second-most toxic and teratogenic of all chemicals tested (rank order of BPAF > TMBPF > BPS > BPA). These results underscore the adverse effects of BPA replacements on early embryo development and may have implications for reproductive health and disease across species, including pregnancy exposures in humans.